2019
DOI: 10.3390/su11154001
|View full text |Cite
|
Sign up to set email alerts
|

Factors that Sustain Health and Safety Management Practices in the Food Industry

Abstract: Due to the significant change in business organizations, scholarly interest has diverted from studying the determinants of financial performance to understanding the environmental activities, sustainability practices, and health and safety management practices. Despite the extensive literature, it is yet to understand either internal or external factors that improve health and safety management practices in SMEs. This research examines the influence of the internal factors—intellectual capital, information tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 73 publications
(131 reference statements)
0
8
0
Order By: Relevance
“…As the figure shows, the keywords of our study are innovation and knowledge, located in the centre of the map. Indeed, these words recur in our data set as a constant throughout the research period ( ex multis Cillo et al , 2019; Coluccia et al , 2019; Frondizi et al , 2019; Hassan et al , 2019; Jardon et al , 2019; Khan et al , 2019; Caldera et al , 2017; Liu, 2017; Lerro et al , 2014; De Leaniz et al , 2013; Curado, 2008; Martín de Castro et al , 2004; Adams et al , 2003; Guthrie, 2001). Then, the words performance, impact, competitive advance, model and business were recurrent in most of the articles examined and are introduced in Table A1 in the Appendix.…”
Section: Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…As the figure shows, the keywords of our study are innovation and knowledge, located in the centre of the map. Indeed, these words recur in our data set as a constant throughout the research period ( ex multis Cillo et al , 2019; Coluccia et al , 2019; Frondizi et al , 2019; Hassan et al , 2019; Jardon et al , 2019; Khan et al , 2019; Caldera et al , 2017; Liu, 2017; Lerro et al , 2014; De Leaniz et al , 2013; Curado, 2008; Martín de Castro et al , 2004; Adams et al , 2003; Guthrie, 2001). Then, the words performance, impact, competitive advance, model and business were recurrent in most of the articles examined and are introduced in Table A1 in the Appendix.…”
Section: Resultsmentioning
confidence: 92%
“…The classification of the articles carried out with Table A1, through the schematisation of the subtitle and the brief description of the purpose of each article, revealed that most of the scholars analysed, in general, the implications that KM can have on the competitiveness of companies, also through the use of NTs (Ardito et al , 2019; Cillo et al , 2019; Coluccia et al , 2019; Santoro et al , 2019; Bresciani et al , 2018; Natalicchio et al , 2017; Xu and Wang, 2018; Lerro et al , 2014; Curado, 2008; Hussi, 2004; Mavridis, 2004; Zhou and Fink, 2003; Guthrie, 2001; Alee, 2000; Liebowitz et al , 2000; Sullivan, 1999). Some have instead studied in particular the implications that the IC has on the prerogatives of SD and the creation of SBMs, whereas sustainability has become a major issue in commercial operations (Hassan et al , 2019; de Villiers and Sharma, 2017; Xu and Wang, 2018; Barth et al , 2017; Caldera et al , 2017; Evans et al , 2017; Liu, 2017; de Leaniz et al , 2013; López-Gamero et al , 2011; Oliveira et al , 2010; Carrillo et al , 2009; Adams et al , 2003; Sharkie, 2003; Malone and Yohe, 2002). Indeed, IC has a fundamental influence on the development prerogatives of companies and is a long-term source of value (de Villiers and Sharma, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations